2011
DOI: 10.1093/cvr/cvr036
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced susceptibility to biomechanical stress in ACE2 null mice is prevented by loss of the p47phox NADPH oxidase subunit

Abstract: In the absence of ACE2, biomechanical stress triggers activation of the myocardial NAPDH oxidase system with a critical role of the p47(phox) subunit. Increased production of superoxide, activation of MMP, and pathological signalling leads to severe adverse myocardial remodelling and dysfunction in ACE2KO mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 44 publications
(61 reference statements)
5
94
0
Order By: Relevance
“…3, 8 For transmission electron microscopic analysis, samples of mice heart tissues (left ventricles) were immediately cut into small pieces and immersed in 2.5% glutaraldehyde as described previously. 19 The myocardial ultrastructure of the WT and ACE2KO mice was observed on a HITACHI-600 electron microscope (Hitachi, Japan).…”
Section: Echocardiography and Myocardial Ultrastructure Observationmentioning
confidence: 99%
“…3, 8 For transmission electron microscopic analysis, samples of mice heart tissues (left ventricles) were immediately cut into small pieces and immersed in 2.5% glutaraldehyde as described previously. 19 The myocardial ultrastructure of the WT and ACE2KO mice was observed on a HITACHI-600 electron microscope (Hitachi, Japan).…”
Section: Echocardiography and Myocardial Ultrastructure Observationmentioning
confidence: 99%
“…3 Angiotensin-converting enzyme 2 (ACE2), a homologue of angiotensin-converting enzyme, is a monocarboxypeptidase that metabolizes Ang II to yield angiotensin 1-7 (Ang 1-7) and lowers the Ang II/Ang 1-7 ratio. [4][5][6][7][8][9] Ang II receptor blockers that selectively antagonize the AT 1 R became a valid alternative approach to interfere with the renin-angiotensin system axis and also upregulates ACE2, resulting in the generation of Ang 1-7. 10,11 Ang 1-7 acts on the Mas receptor and plays an important role in counteracting the actions of Ang II.…”
mentioning
confidence: 99%
“…10,11 Ang 1-7 acts on the Mas receptor and plays an important role in counteracting the actions of Ang II. [12][13][14][15][16][17][18] Ang II-mediated oxidative stress, cardiac hypertrophy, contractile dysfunction, and fibrosis are exacerbated in ACE2-deficient mice, 5,7 whereas recombinant human ACE2 is able to attenuate these responses and improve cardiac function, with a marked reversal of Ang II-mediated signaling. 6 Many of the cardiac pathological effects of reninangiotensin system activation and Ang II appear to be mediated through ROS, produced by a specific NADPH oxidase-dependent pathway in an AT 1 R-dependent manner.…”
mentioning
confidence: 99%
“…6 Aortic banding of ACE2KO mice exacerbates the progression of LV hypertrophy, LV dilatation, and systolic dysfunction, which is associated with increased NADPH oxidase activity and subsequent oxidative stress, and is amendable to reversal following Ang 1-7 supplementation. 7 Utilizing a different approach, Mercure et al also demonstrated beneficial effects for Ang 1-7 against Ang II-induced adverse remodeling, as transgenic mice that overexpress Ang 1-7 specifically in the heart exhibit a reduction in ventricular fibrosis and LV hypertrophy following a 19-day Ang II infusion. 8 In the Patel et al study, the authors crossed ACE2KO mice with diabetic Akita mice to determine the contribution of ACE2 in the progression of diabetic cardiomyopathy.…”
Section: Article See P 1322mentioning
confidence: 99%